2017
DOI: 10.1136/bmjopen-2016-015386
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant preterm birth and severe small-for-gestational age birth weight among infants of immigrant mothers in Ontario originating from the Philippines and East Asia: a population-based study

Abstract: ObjectivesWomen from the Philippines form one of the largest immigrant groups to North America. Their newborns experience higher rates of preterm birth (PTB), and separately, small-for-gestational age (SGA) birth weight, compared with other East Asians. It is not known if Filipino women are at elevated risk of concomitant PTB and severe SGA (PTB–SGA), a pathological state likely reflective of placental dysfunction and neonatal morbidity.MethodsWe conducted a population-based study of all singleton or twin live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…In a previous study, Filipinos in Japan were reported to have the highest infant and fetal mortality rates [12]. A similar high risk among mothers from the Philippines has been observed in Canada and Korea [5,23]. In addition, in this study, a high risk for preterm birth was observed among mothers from Brazil and other countries.…”
Section: Discussionsupporting
confidence: 83%
“…In a previous study, Filipinos in Japan were reported to have the highest infant and fetal mortality rates [12]. A similar high risk among mothers from the Philippines has been observed in Canada and Korea [5,23]. In addition, in this study, a high risk for preterm birth was observed among mothers from Brazil and other countries.…”
Section: Discussionsupporting
confidence: 83%
“…We will retrospectively evaluate adverse pregnancy outcomes among Ontario women physicians and nonphysicians of reproductive age who have experienced at least one childbirth >20 weeks GA. All outcomes of interest were chosen for their clinical relevance and established methodology for ascertainment from ICES databases such as MOMBABY, DAD and OHIP, using standard diagnostic and procedural codes [46][47][48][49][50][51][52][53][54] (see online supplemental table 3).…”
Section: Discussionmentioning
confidence: 99%
“…and/or Ontario-specific algorithms to ensure accuracy [46][47][48][49][50][51][52][53][54] ; and have used databases that are validated 55 56 or periodically reabstracted. 57 Aim 1: compare reproductive patterns in women physicians and non-physicians Rationale and overview Numerous survey-based studies suggest that women physicians frequently delay childbearing and subsequently experience a higher rate of infertility compared with the general population.…”
Section: Open Accessmentioning
confidence: 99%
“…Vaxtarskerðing fósturs og fyrirburafaeðingar haldast oft í hendur en í þessari rannsókn var vaxtarskerðing einungis haerri hjá konum í mið-HDI hópnum miðað við íslenskar konur. Það er í samraemi við niðurstöður rannsóknar 32 sem sýndi mun á tíðni eftir upprunalandi og niðurstöður frá Ástralíu 1 og Danmörku. 7 Sjálfkrafa fyrirburafaeðing var algengari hjá konum í mið-og laegsta-HDI-hópnum en hins vegar var fyrirburafaeðing mark-taekt sjaldnar framkölluð hjá konum í laegsta-HDI-hópnum.…”
Section: Umraeðaunclassified